2014
DOI: 10.1007/s00380-014-0553-0
|View full text |Cite
|
Sign up to set email alerts
|

Is pentraxin 3 a biomarker, a player, or both in the context of coronary atherosclerosis and metabolic factors?

Abstract: The objective of this study is to determine whether pentraxin-3 (PTX-3) is clinically a biomarker of inflammation, a player in anti-inflammation, or both with regard to coronary atherosclerosis, we compared levels of PTX-3 with levels of adiponectin in addition to high-sensitivity C-reactive protein (hs-CRP). We enrolled 693 patients (51 % male; mean age 64 ± 12 years) at Fukuoka University Hospital. They were clinically suspected to have coronary artery disease (CAD) or had at least one cardiac risk factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…For example, a proatherogenic role has been suggested for PTX3 in metabolic diseases [54, 55]. In contrast, the work of Nakamura et al [56] in coronary artery disease patients showed that PTX3 correlates to body fat and lipid profile in a comparable way to adiponectin—an atheroprotective adipokine— and opposite to CRP. Furthermore, in vivo studies showed that PTX3 is cardioprotective in acute myocardial infarction [57], while deficiency in this pentraxin promotes both vascular inflammation and atherosclerosis in mice [15].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a proatherogenic role has been suggested for PTX3 in metabolic diseases [54, 55]. In contrast, the work of Nakamura et al [56] in coronary artery disease patients showed that PTX3 correlates to body fat and lipid profile in a comparable way to adiponectin—an atheroprotective adipokine— and opposite to CRP. Furthermore, in vivo studies showed that PTX3 is cardioprotective in acute myocardial infarction [57], while deficiency in this pentraxin promotes both vascular inflammation and atherosclerosis in mice [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of CVDs, inflammation plays a key role. [ 30 31 ] The serum level of hs-CRP cytokine increases in inflammatory conditions[ 5 ] and is related to developing CVDs. [ 32 ] In addition, CoQ10 influences inflammatory factors such as cytokines, so it can be useful for treating CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been extensive recent studies investigating the roles of PTX-3 in vascular disease and angiogenesis [30, 31]. PTX-3 is produced not only by vascular smooth muscle cells and endothelial cells with localized inflammation but also by macrophages and monocytes in invasive lesions [23].…”
Section: Discussionmentioning
confidence: 99%